EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK TEKNIK PROBLEM SOLVING UNTUK MENINGKATKAN PERENCANAAN KARIR SISWA SMK - Cicilia Sekar Agustie; Elisabeth Christiana; Wiryo Nuryono (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
Career planning is an important aspect of guidance and counseling services in Vocational High Schools (SMK) because it is closely related to students’ readiness in determining further education and entering the world of work. However, in reality, many students still experience difficulties in planning their careers effectively. This condition is caused by a lack of self-understanding, limited career information, and inadequate ability to make career decisions. This study aims to determine the effectiveness of group guidance services using the problem-solving technique in improving the career planning of vocational high school students. This research employed a quantitative approach with a quasi-experimental design using a pretest–posttest model. The research subjects were eleventh-grade vocational high school students who had low to moderate levels of career planning. Data were collected using a career planning scale that had been tested for validity and reliability. Data analysis was conducted using statistical tests to compare the results before and after the implementation of the service. The results showed a significant increase in students’ career planning levels after participating in group guidance services using the problem-solving technique. These findings indicate that group guidance services with the problem-solving technique are effective in helping students understand their potential, identify various career alternatives, and make more directed career decisions. Therefore, this service can be used as a strategy by guidance and counseling teachers to improve the career planning abilities of vocational high school students. ABSTRAK Perencanaan karier merupakan salah satu aspek penting dalam layanan bimbingan dan konseling di Sekolah Menengah Kejuruan (SMK) karena berkaitan dengan kesiapan siswa dalam menentukan pilihan studi lanjut maupun dunia kerja. Namun, pada kenyataannya masih banyak siswa yang mengalami kesulitan dalam merencanakan karier secara matang akibat kurangnya pemahaman diri, informasi karier, serta kemampuan dalam mengambil keputusan. Penelitian ini bertujuan untuk mengetahui efektivitas layanan bimbingan kelompok dengan teknik problem solving dalam meningkatkan perencanaan karier siswa SMK. Penelitian ini menggunakan pendekatan kuantitatif dengan desain eksperimen semu (quasi experimental design) dengan model pretest-posttest. Subjek penelitian adalah siswa kelas XI SMK yang memiliki tingkat perencanaan karier rendah hingga sedang. Pengumpulan data menggunakan skala perencanaan karier yang telah diuji validitas dan reliabilitasnya. Teknik analisis data menggunakan uji statistik untuk membandingkan hasil sebelum dan sesudah pemberian layanan. Hasil penelitian menunjukkan bahwa terdapat peningkatan yang signifikan pada tingkat perencanaan karier siswa setelah mengikuti layanan bimbingan kelompok dengan teknik problem solving. Temuan ini menunjukkan bahwa layanan bimbingan kelompok dengan teknik problem solving efektif dalam membantu siswa memahami potensi diri, mengidentifikasi berbagai alternatif karier, serta mengambil keputusan karier secara lebih terarah. Dengan demikian, layanan ini dapat menjadi salah satu strategi yang dapat diterapkan oleh guru bimbingan dan konseling dalam meningkatkan kemampuan perencanaan karier siswa SMK.